2020
DOI: 10.1038/s42004-020-00368-z
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic kinetic resolution of desmethylphosphinothricin indicates that phosphinic group is a bioisostere of carboxyl group

Abstract: Escherichia coli glutamate decarboxylase (EcGadB), a pyridoxal 5'-phosphate (PLP)-dependent enzyme, is highly specific for L-glutamate and was demonstrated to be effectively immobilised for the production of γ-aminobutyric acid (GABA), its decarboxylation product. Herein we show that EcGadB quantitatively decarboxylates the L-isomer of D,L-2-amino-4-(hydroxyphosphinyl)butyric acid (D,L-Glu-γ-P H), a phosphinic analogue of glutamate containing C-P-H bonds. This yields 3-aminopropylphosphinic acid (GABA-P H), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…However, substrate promiscuity has been seen in GADs from different domains of life. For example, E. coli GAD was able to convert a phosphinic analog of glutamate to a phosphinic analog of GABA 70 . In addition, human and other mammalian GADs are known to catalyze decarboxylation of substrates other than L-glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…However, substrate promiscuity has been seen in GADs from different domains of life. For example, E. coli GAD was able to convert a phosphinic analog of glutamate to a phosphinic analog of GABA 70 . In addition, human and other mammalian GADs are known to catalyze decarboxylation of substrates other than L-glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration of 90% colony-forming units (MIC 90 ) of the test strain E. coli K12 MG1655 was determined by the broth microdilution method in the minimal medium EG containing MgSO4•7H 2 O (0.2 g), citric acid•H 2 O (2.0 g), anhydrous K 2 HPO 4 (10.0 g), NaNH 4 HPO 4 •H 2 O (3.5 g), and glucose (4.0 g), milliQ water (1.0 L) final pH 7, prepared as described earlier [ 40 ]. Briefly, overnight cultures (2 mL) of E. coli K12 strain MG1655 were centrifuged at 3500 rpm for 15 min at 15 °C and the cell pellets resuspended in an equivalent volume of physiological solution (9 g/L NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…The minimum inhibitory concentration able to inhibit 90% (MIC 90 ) of the the growth of the bacterial population of the test strain E. coli K12 MG1655 was calculated using the broth microdilution method in the minimal medium EG containing MgSO 4 •7H 2 O (0.2 g), citric acid•H 2 O (2.0 g), anhydrous K 2 HPO 4 (10.0 g), NaNH 4 HPO 4 •H 2 O (3.5 g), and glucose (4.0 g), milliQ water (1.0 L), at a final pH of 7.0 as described elsewhere [19]. Briefly, overnight cultures (2 mL) of the E. coli K12 strain MG1655 grown in LB (lysigeny broth) medium were centrifuged at 3500 rpm for 15 min at 15 • C and the bacterial cellular pellets resuspended in an isovolume of saline solution (9 g/L NaCl).…”
Section: The Microdilution Methods To Determine the Antimicrobial Act...mentioning
confidence: 99%
“…To date, the mechanism of antibacterial activity of L-Glu-γ-P H remains unknown; however, we demonstrated that the H-phosphinic group of L-Glu-γ-P H is a bioisostere of carboxylates, and that the desmethylated phosphinic compounds derived from it (i.e., the H-phosphinic analogues of GABA and succinate) can be recognized and metabolized just as the substrate by the relevant enzymes [19]. We also found that only the L-isomer of Glu-γ-P H displays an antibacterial activity, which implies that the compound is indeed metabolized and leads to the formation of intermediate(s) eventually responsible for the observed antibacterial activity [19]. To the best of our knowledge, peptides containing amino acids with a H-phosphinic group in a distal position from the carboxyl group have never been investigated as antibacterials.…”
Section: Introductionmentioning
confidence: 94%